Peningkatan kemampuan koneksi dan komunikasi matematik melalui model pembelajaran kooperatif tipe two stay two stray - Ebih Abdul Rachim Arhasy; Yeni Heryani (Program Studi Pendidikan Matematika, FKIP, Universitas Siliwangi, Tasikmalaya, 2015)
This research focused on the implementation of Cooperative Learning type, Two Stay Two Stray. The aims of study were to determine the better gain of students’ Mathematical Connections and Communications treated by Cooperative Learning Model type Two Stay Two Stray and direct learning model, also at which level of students’ Mathematical ability the model become effective? The populations in this study were all bachelors’ degree of Mathematics Department in academic year 2013-2014, and then two of five classes were taken as the sample of research. The instrument used in this study includes the test of Mathematical Connection and Communication. Analysis of data used two different test averages and One Way Anova with Scheffe test. The result of the study has been found that the improvement of Mathematical Connection and Communication of students who obtained Cooperative Learning Model type Two Stay Two Stray is better than Direct Learning Model. The improvement of Mathematical Communication and Connections in high group of students was better than medium and low group.